Genome‐wide interaction study of early‐life smoking exposure on time‐to‐asthma onset in childhood. Issue 10 (9th October 2019) - Sugier, Pierre‐Emmanuel; Sarnowski, Chloé; Granell, Raquel; Laprise, Catherine; Ege, Markus J.; Margaritte‐Jeannin, Patricia; Dizier, Marie‐Hélène; Minelli, Cosetta; Moffatt, Miriam F.; Lathrop, Mark; Cookson, William O. C. M.; Henderson, A. John; et al.
Abstract: Background: Asthma, a heterogeneous disease with variable age of onset, results from the interplay between genetic and environmental factors. Early‐life tobacco smoke (ELTS) exposure is a major asthma risk factor. Only a few genetic loci have been reported to interact with ELTS exposure in asthma. Objective: Our aim was to identify new loci interacting with ELTS exposure on time‐to‐asthma onset (TAO) in childhood. Methods: We conducted genome‐wide interaction analyses of ELTS exposure on time‐to‐asthma onset in childhood in five European‐ancestry studies (totalling 8273 subjects) using Cox proportional‐hazard model. The results of all five genome‐wide analyses were meta‐analysed. Results: The 13q21 locus showed genome‐wide significant interaction with ELTS exposure ( P  = 4.3 × 10 −8 for rs7334050 within KLHL1 with consistent results across the five studies). Suggestive interactions ( P  < 5 × 10 −6 ) were found at three other loci: 20p12 (rs13037508 within MACROD2 ; P  = 4.9 × 10 −7 ), 14q22 (rs7493885 near NIN ; P  = 2.9 × 10 −6 ) and 2p22 (rs232542 near CYP1B1 ; P  = 4.1 × 10 −6 ). Functional annotations and the literature showed that the lead SNPs at these four loci influence DNA methylation in the blood and are located nearby CpG sites reported to be associated with exposure to tobacco smoke components, which strongly support our findings. Conclusions and Clinical Relevance: We identified novel candidate genes interacting with ELTS exposure on time‐to‐asthma onset in childhood. These genes have plausible biological relevance related to tobacco smoke exposure. Further epigenetic and functional studies are needed to confirm these findings and to shed light on the underlying mechanisms.